Running safety evaluation of a train moving over a high-speed railway viaduct under different track conditions. (March 2021) - Peixer, M.A.; Montenegro, P.A.; Carvalho, H.; Ribeiro, D.; Bittencourt, T.N.; Calçada, R.
Highlights: Running safety of train moving in a continuous viaduct with different track conditions. Train structure interaction method to analyze dynamic the coupling system. Comparison of track indexes for real and perfect rigid bridge. Good agreement between results and the limits proposed by European codes. Viaduct flexibility did not influence the results with respect to the derailment risk. Abstract: This paper addresses the evaluation of the running safety of high–speed (HS) train moving over a continuous viaduct with different track conditions, ranging from very well-maintained to the worst condition possible according to the European recommendations, referred to as the safety limit. The case study focuses on the "La Scarpe" viaduct, which consists of a continuous nine-span steel–concrete composite bridge belonging to the French HS railway line TGV Nord, and on the German HS train ICE3 composed by eight independent cars. Firstly, the analysis is carried out considering the flexibility of the viaduct through train–bridge interaction (TBI) coupling system, where the running safety is analyzed according to Nadal, Prud'homme and Unload criteria. The results are then compared with those obtained using a rigid structure, which allowed to draw important conclusions regarding the effects of the viaduct's vibrations. From the results it was possible to conclude that the criteria have shown a good agreement with the limits laid down in the European norms. In addition, it was also possible to assume that the viaduct flexibility did not influence the results with respect to the derailment risk. Thus, for this particular case study, the train running safety assessment could be carried out using a simpler rigid structure model, which considerably reduces the degrees of freedom and the problem complexity without losing accuracy.